The Role of Scheduling in Reducing Delays in Infrastructure Projects - Alhamza Ahmed Hasan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Large delays in infrastructure projects may lead to budget overruns, worse quality, and stakeholder dissatisfaction. This study examines scheduling tools and methods to decrease delays in large infrastructure projects. It compared Primavera P6 and MS Project projects with traditional scheduling methods. Detailed case studies indicate that improved scheduling improves project timetables, resource allocation, and cost management. Results demonstrate that advanced scheduling may boost project productivity and save delays by 50%. At the study's conclusion, risk management, real-time tracking, and critical path analysis were suggested for scheduling.